ダイ42ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 2000-2001 - 加藤, 好孝; カトウ, ヨシタカ; Kato, Yoshitaka (2002)
P(論文) 第42次南極地域観測隊夏隊20名は、越冬隊40名、同行者5名(環境庁1名、報道1名、大学院生1名、中国およびスロバキアからの交換科学者2名)とともに合計65名で2000年11月14日南極観測船「しらせ」にて東京港を出港し、船上および南極地域において各種観測・設営活動を行い、翌2002年3月28日に成田空港に帰国した。 往路においては海洋観測に加え、アムンゼン湾リーセル・ラルセン山での地学調査隊の送り込みとその支援活動を行った後、12月30日に「しらせ」は昭和基地に接岸した。それに先立ちヘリコプターにより第1便を昭和基地へ、また内陸旅行隊の人員物資をS16へ空輸した。昭和基地接岸後は、物資輸送、持ち帰り物資の積み込み、建設作業、沿岸野外調査などを実施した。昭和基地への輸送物資量は1049トンに達した。基地における建設作業として、光学観測棟、焼却炉棟、廃棄物集積場、西部地区分電盤小屋、送油ポンプ小屋、配管メンテナンス抗等の新築作業に加え、燃料タンクの新設・移設、太陽熱温水器の設置、防油堤の設置、旧食堂棟の撤去、倉庫棟および防火区画Aの屋根補修、大型アンテナレドームの補修など大小合わせて25項目、53日間にわたる延べ2440人日の作業を実施した。また夏期観測として、生物、海洋、地学、海洋、宙空、気象などの沿岸調査をリュツオ・ホルム湾露岩域を中心に実施した。夏隊・同行者合計20名は2001年2月15日までに「しらせ」に戻った。帰路においては、リーセル・ラルセン山の地学パーティーを収容するとともに、同地域およびトナー島に残置されていた建物・設備をすべて撤収し、海洋観測を実施しつつ「しらせ」は3月21日にシドニー港に入港、観測隊は3月28日に空路帰国した。 The summer party of the 42nd Japanese Antaractic Research Expedition (JARE-42), including 20 expeditioners and 5 observers (an Environemntal Agency officer, a journalist, a graduate student, and two foreign exchange scientists from China and Slovakia), left Tokyo for Antarctica on 14 November 2000 on board Shirase with wintering team of 40 expeditioners. We conducted oceanographical observations, various scientific activities and logistical operations in the Antarctic regions, and retuned to Japan on 28 March 2001. On the way to Syowa Station, geological team was transported by the helicopters to Mt. Riiser-Larsen to conduct their science programs during the summer season. On 30 December, Shirase anchored at Syowa Station and 1049 tons of cargo was unloaded by the helicopters and the surface vehicles. Prior to that, preparation flights to Syowa Station and opereation to support the inland traverse party at S16 were carried out. At Syowa Station, construction of new buildings, meaintenance of station facilities, suppport of field operations, etc. were conducted. After the completion of construction and field operations, the JARE-42 summer party left Syowa Station on 15 February 2001. On the way to Sydney, geological team was picked up from Mt. Riiser-Larsen, and all remained ...